EURO-B.O.S.S.: a European study on chemotherapy in bone-sarcoma patients aged over 40: outcome in primary high-grade osteosarcoma - Ferrari, Stefano; Egerer, Gerlinde (Tumori journal, 2018)
Introduction:The EUROpean Bone Over 40 Sarcoma Study (EURO-B.O.S.S.) was the first prospective international study for patients 41-65 years old with high-grade bone sarcoma treated with an intensive chemotherapy regimen derived from protocols for younger patients with high-grade skeletal osteosarcoma.Methods:Chemotherapy based on doxorubicin, cisplatin, ifosfamide, and methotrexate was suggested, but patients treated with other regimens at the investigators? choice were also eligible for the study.Results:The present report focuses on the subgroup of 218 patients with primary high-grade osteosarcoma. With a median follow-up of 47 months, the 5-year probability of overall survival (OS) was 66% in patients with localized disease and 22% in case of synchronous metastases. The 5-year OS in patients with localized disease was 29% in pelvic tumors, and 70% and 73% for extremity or craniofacial locations, respectively.In primary chemotherapy, tumor necrosis ≥90% was reported in 21% of the patients. There were no toxic deaths; however, hematological toxicity was considerable with 32% of patients experiencing 1 or more episodes of neutropenic fever. The incidence of nephrotoxicity and neurotoxicity (mainly peripheral) was 28% and 24%, respectively. After methotrexate, 23% of patients experienced delayed excretion, in 4 cases with nephrotoxicity.Conclusions:In patients over 40 years of age with primary high-grade osteosarcoma, an aggressive approach with chemotherapy and surgery can offer the probability of survival similar to that achieved in younger patients. Chemotherapy-related toxicity is significant and generally higher than that reported in younger cohorts of osteosarcoma patients treated with more intensive regimens.
Published online: December 5, 2017
Gesehen am 30.08.2019